Development of a new software and test setup for analyzing hVOR in very young children by vHIT - Schell, Angela; Eck, Simon; Rohr, Karl; Hörmann, Karl; Hülse, Manfred; Hülse, Carl Roland (Journal of vestibular research, 2017)
INTRODUCTION: Earlier work revealed that vHIT examination is often difficult to perform on very young children. In particular, the calibration of the system can be difficult, as active cooperation of the patient is required. Additionally, the patient must be able to follow the examiner’s instructions, which is challenging for very young children. Therefore, the aim of the present study was to develop and validate a new, software-based approach enabling vHIT testing of young children and infants. METHODS AND MATERIALS: Six patients (3 boys and 3 girls) aged 5–36 months were included in a prospective, monocentric study between January 2015 and August 2015. The newly developed intuitive software enabled calibration of the eye position signal with the subjects fixating on animated animal graphics which were projected on a screen. Testing ten healthy adults validated this new calibration and measurement method. After calibration, a vHIT goggle (EyeSeeCam ©) was used to perform head impulses in the horizontal plane while the patient was watching a movie sitting on their parent’s lap or in a baby chair. At least 15 impulses to each side were obtained and the occurrence of refixation saccades was analyzed. All tests were performed by one of two experienced examiners. RESULTS: The new calibration method and modified test setup provided reproducible results for all patients tested. An increased incidence of artifacts was not observed. In 2 patients, more than one test was needed. None of the included children showed catch-up overt or catch-up covert saccades. There was no gain reduction of more than two standard deviations as compared to the normative results published in the literature on vHIT examinations of children. CONCLUSION: The proposed protocol allows vHIT testing in very young children and infants (aged 5 months to 3 years). The study emphasizes that vHIT is an easy and sensitive screening tool to evaluate vestibular function in children and should be used as the gold standard in pediatric vestibular assessment.
Gesehen am 09.05.2018